Fine-root biomass production, sedge root, sedge leaf, and moss shoot decomposition, soil water-table level, and temperature data from two sedge fens in Finland ... - Bhuiyan, Rabbil; Mäkiranta, Päivi; Straková, Petra; Fritze, Hannu; Minkkinen, Kari; Penttilä, Timo; Tuittila, Eeva-Stiina; Laiho, Raija (Zenodo, 2022)
Dataset including fine-root biomass production, mass loss of sedge (Carex rostrata) roots and leaves, and moss (Sphagnum fallax) shoots, along with environmental data (soil water-table level, air temperature, soil temperature at 5 cm, and soil temperature at 15 cm) from two sedge fens located in southern Finland (Lakkasuo, Orivesi, 61°48' N 24°19'E) and northern Finland (Lompolojänkkä, Kittilä, 68°N 24°12'E). Data are from a climate change experiment, where warming was induced with open top chambers (OTCs) and drying with shallow ditching. Data are from years 2011-2013. ...